Functional profiling of bisphenols for nuclear receptors. (15th May 2019) - Grimaldi, Marina; Boulahtouf, Abdelhay; Toporova, Lucia; Balaguer, Patrick
Highlights: We showed that bisphenols act essentially as ERs, ERRγ and PXR activators and AR, GR, PR and MR antagonists. We also showed that some bisphenols can bind to several NRs whereas other bisphenols interact with fewer NRs. Abstract: Bisphenol-A (BPA) is one of the most abundant chemicals produced worldwide. Exposure to BPA has been associated with various physiological dysregulations, involving reproduction, development, metabolism, as well as genesis and progression of hormone-dependent cancers. It has been well published that BPA along with its analogs bind and activate estrogen receptors (ER) α and β, estrogen related receptor (ERR) γ and pregnan X receptor (PXR). BPA has been also characterized as an inhibitor of the androgen (AR) and progesterone (PR) receptor. Thus, the need for safer alternatives to BPA among bisphenols is rising. In this regard, we used reporter cell lines to analyze the effects of 24 bisphenols on the selected nuclear receptors (NRs), known and potential targets of BPA. We showed that bisphenols differently modulated the activities of NRs. ERs, ERRγ and PXR were generally activated by bisphenols, whereas many compounds of this family acted as AR, PR, GR and MR antagonists. On the other hand, some bisphenols such as BPA, BPC and BPE modulated the activity of several NRs, but others lacked the activity of other NRs. Altogether, these data provide the guidelines for development of safer BPA substitutes with reduced hormonal activity.